A novel method for the removal of epoxy coating from waste printed circuit board. Issue 7 (July 2018) - Senophiyah-Mary, J; Loganath, R; Meenambal, T
The printed circuit board, which is the heart of all electronic devices, is a rich source of metal, which could act as a future resource. Bioleaching, a biological treatment, would be an appropriate method for the environmentally sound management of e-waste. Various strippers are used to remove the epoxy coating and it is harmful to remove the epoxy coating with those solvents and salts in the open because of the presence of brominated flame retardants on the surface of the printed circuit board, which leads to serious health issues. An alternate process is required to remove the epoxy coating thereby enhancing the bioleaching process. Sonication is the process of applying sound energy to agitate particles in a solvent bath. The combined process of sonication and solvent stripping in a closed environment could decrease the time for stripping the epoxy coating. An attempt has been made to optimise the stripping agent for the removal of epoxy coating and from the experiment it was found that bath sonication could easily remove the epoxy coating from the waste printed circuit board with no emission of toxic gases. An optimum time of 5 min was enough for the stripping process prior to the soak time of 8 h at 5 N NaOH solution, while a longer time and high concentration of chemicals would be required to remove the epoxy coating with usual methods.